Insectlopedia : poems and paintings - Florian, Douglas (San Diego : Harcourt, 2002)
Presents twenty-one short poems about such insects as the inchworm, termite, cricket, and daddy longlegs.
"Voyager books."
Elem. School Library Collection
School Library Journal starred
Wilson's Children
3.3
3-6
Keywords: Children's poetry, American; Insects in art -- Juvenile literature; Insects -- Juvenile poetry; American poetry; Insects -- Poetry; American poetry; Insects -- Poetry